2022
DOI: 10.1002/cphc.202200109
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide Ion Mechanism for Long‐Range Proton Pumping in the Third Proton Transfer of Bacteriorhodopsin

Abstract: In bacteriorhodopsin, representative light‐driven proton pump, five proton transfers yield vectorial active proton translocation, resulting in a proton gradient in microbes. Third proton transfer occurs from Asp96 to the Schiff base on the photocycle, which is expected to be a long‐range proton transfer via the Grotthuss mechanism through internal water molecules. Here, large‐scale quantum molecular dynamics simulations are performed for the third proton transfer, where all the atoms (∼50000 atoms) are treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…This limitation causes the system to become trapped in one of the abundant local minima and makes it impractical to access reliable physical quantities, including the free-energy landscape. The improved sampling of rare events under investigation can be addressed by combining it with the so-called enhanced sampling methods. Among several popular enhanced sampling methods, some of our calculations ,,, have relied on the metadynamics (MTD) technique. The MTD method biases the dynamics by frequently depositing repulsive potentials in the space of predefined collective variables (CVs). The accumulated bias potentials become a negative value of the free-energy surface (FES) along the CV if the simulation is sufficiently long.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…This limitation causes the system to become trapped in one of the abundant local minima and makes it impractical to access reliable physical quantities, including the free-energy landscape. The improved sampling of rare events under investigation can be addressed by combining it with the so-called enhanced sampling methods. Among several popular enhanced sampling methods, some of our calculations ,,, have relied on the metadynamics (MTD) technique. The MTD method biases the dynamics by frequently depositing repulsive potentials in the space of predefined collective variables (CVs). The accumulated bias potentials become a negative value of the free-energy surface (FES) along the CV if the simulation is sufficiently long.…”
Section: Theorymentioning
confidence: 99%
“…The performance of MTD can be improved with advanced algorithms such as well-tempered (WT) and multiple walkers (MW) variants in terms of the smooth convergence of FES and sampling efficiency, respectively. Our latest applications demonstrated that DC-based QM-MD/MTD simulations could treat chemical reactions in condensed-phase systems containing more than 10 4 atoms. …”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…These three-dimensional information with atomic resolution enabled a theoretician to analyze the proton transfer mechanism in BR using a quantum mechanics method. Dr. Junichi Ono (the fifth speaker of the session 5) focused on the proton transfer reactions in BR and revealed hydronium (H3O + ) and hydroxide (OH − ) ions are involved [39][40][41]. Namely, in the first proton transfer from the PRSB to D85, it was proposed that a transiently formed hydroxide ion pulled a proton from the PRSB [39].…”
mentioning
confidence: 99%